Peningkatan Prestasi Belajar Siswa pada Pembelajaran Tematik dengan Metode Demontrasi pada Kelas 1 SD N Tepus 1 - Eknu Sriyani; Sukadari Sukadari (UM Purwokerto Press, 2022)
The purpose of the research is to improve student achievement in thematic learning with the demonstration method in class 1 SDN Tepus 1. This research is a class action research (classroom action research). The research subjects were the first grade students of SDN Tepus 1 Gunungkidul Regency for the academic year 2021/2022 (22 students), comprising of 14 boys and 8 girls. Data processing techniques are using observation, tests and documentation. The data analysis technique used data triangulation, by comparing the increase in the acquisition of student scores as illustrated by the pre and post test data. The results showed an increase in student learning activity, namely: (1) In cycle 1, 10 students (45.45%) achieved mastery learning; (2) In cycle II, 19 students (86.36%) were able to achieve complete learning; and (3) In cycle III, 22 students (100%) were able to achieve complete learning.